PENGARUH KONSENTRASI JAHE PADA MINUMAN HERBAL KAPULAGA DAN GULA SEMUT AREN TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK - M. Sa'roni (Ekliptika, 2023)
Herbal drink is a cultural heritage that is very useful for boosting immunity. Until now, many people still choose to consume herbal drinks because they are sourced from natural ingredients so they do not cause side effects and harmful reactions to the body. This research is a study to determine the chemical and organoleptic characteristics of herbal drinks made from ginger, cardamom and palm sugar. This study also used a completely randomized design (CRD) with 5 treatments and 3 replications. The treatments were A1 (3.5 gram ginger, 0.25 gram cardamom and 30 gram palm sugar), A2 (3 gram ginger, 0.25 gram cardamom and 30 gram palm sugar), A3 (2.5 gram ginger, 0.25 gram cardamom and 30 gram palm sugar), A4 (2 gram ginger, 0.25 gram cardamom and 30 gram palm sugar), A5 (Ginger 1.5 grams, 0.25 grams of cardamom and 30 grams of palm sugar). Observational data were analyzed using the Anova test with the Minitab application. Based on the results of the chemical and organoleptic characteristic tests, it was determined that the best treatment for herbal drinks made from ginger, cardamom and palm sugar was A5 treatment (mixing 1.5 gram ginger powder, 0.25 gram cardamom powder and 30 gram palm sugar) with chemical characteristics of water content 2.0%, ash content 0.175%, total dissolved solids 97.8 (unit°brix) and panelist acceptance of taste (4.2), aroma (3.5), texture (3.5), color (3.8) and solubility (3.8).